NACOBRICK: Natural Concrete Brick - Zulfa Firdausi Husna; Siti Yanuar Arofah; Nurfi Misyka; Fayyaza Amalia Islami; Ilma Khairunissa (Jurnal Integrasi Sains dan Quran, 2023)
Indonesia is the second agrarian country in the world, produces a very large agricultural waste. However, this has not been used optimally. Examples are egg shell waste, coconut fiber and bagasse. Bagasse waste has a high fiber content. Meanwhile, coconut coir contains cellulose and lignin which makes coconut coir less brittle. The purpose of this study was to determine the effectiveness of Nacobrick as an environmentally safe brick innovation. This type of research is a qualitative descriptive study where the focus of the description is on making brick innovations. The method of collection is through observation. The tests carried out are the water absorption test, the visible properties test, the compressive strength test, and the specific gravity test. The data obtained in this study were analyzed using descriptive methods. Based on the tests carried out, the results obtained details of the size of 30cm x10cmx15cm, with no defects on the outside. The compressive strength value is 25,074 kg/cm2 and the water absorption value is 14.8%. This study succeeded in identifying the effectiveness of Nacobrick on the effectiveness of environmentally friendly bricks as an environmentally safe brick innovation.